Economic value of extended-window intravenous alteplase in posterior circulation stroke: a Markov analysis based on the EXPECTS trial - Ma, Yudong; Lou, Yake; Chen, Maolin; Zeng, Yuhong (Frontiers in Pharmacology, 2026)
ObjectiveTo evaluate the cost-effectiveness of intravenous alteplase compared with standard medical therapy alone for patients with posterior circulation ischemic stroke (PCIS) presenting 4.5–24 h after symptom onset, from the perspective of the Chinese healthcare system.MethodsA hybrid decision tree and Markov model was developed to simulate disease progression over a lifetime horizon (30 years). Clinical efficacy, utility values, and cost data were derived from the EXPECTS randomized controlled trial and domestic database. The primary outcome was the incremental cost-effectiveness ratio (ICER), expressed as cost per quality-adjusted life year (QALY) gained. Cost-effectiveness was assessed against a willingness-to-pay (WTP) threshold of one time China’s per capita GDP (95,749 CNY). One-way and probabilistic sensitivity analyses were performed to test robustness of results.ResultsCompared with standard therapy, alteplase provided an additional 0.95 QALYs at an incremental cost of 17,580 CNY, resulting in an ICER of 18,567 CNY per QALY gained. This ICER is substantially below the WTP threshold, indicating that alteplase is highly cost-effective. The one-way sensitivity analysis showed that the ICER was most sensitive to the risk ratios of disability outcomes (mRS 2–5), yet remained within the cost-effective range across all parameter variations. The probabilistic sensitivity analysis confirmed that at the WTP threshold of 35,000 CNY per QALY, the probability of alteplase being cost-effective was nearly 100%.ConclusionFor patients with PCIS in the 4.5–24-h time window, intravenous alteplase is a highly cost-effective treatment option in China. This finding supports the broader implementation of extended-window thrombolysis for eligible PCIS patients, particularly in settings where access to endovascular thrombectomy or advanced perfusion imaging is limited.